Sex-related differences in primary intracerebral hemorrhage. (19th July 2016) - Roquer, Jaume; Rodríguez-Campello, Ana; Jiménez-Conde, Jordi; Cuadrado-Godia, Elisa; Giralt-Steinhauer, Eva; Vivanco Hidalgo, Rosa María; Soriano, Carol; Ois, Angel
Abstract : Objective: Little information is available about sex-related differences in intracerebral hemorrhage (ICH). This is a prospective observational study to describe the sex differences in demographics, vascular risk factors, stroke care, and outcomes in primary ICH. Methods: BasicMar is a hospital-based registry of all stroke patients admitted to a single public hospital that covers a population of 330, 000. From 2005 to 2015, there were 515 consecutive acute primary ICH patients. Outcome data were obtained at 3 months. Results: More men than women had ICH (52.4% vs 47.6%); the women were older and had worse previous functional status than men, who were more likely to drink alcohol and smoke and to have ischemic heart disease and peripheral arterial disease. There were no sex differences in etiology, severity, or hemorrhage volume. ICH score was greater in women than in men ( p = 0.018). Women had more lobar ICH than men (odds ratio adjusted by age was 1.75 [95% confidence interval 1.18–2.58], p = 0.005). The quality of stroke care was similar in both sexes. Mortality at 3 months was 44.1% in women and 41.1% in men ( p = 0.656), and 3-month poor outcome among survivors (modified Rankin Scale [mRS] score 3–5) 58.4% in women and 45.3% in men ( p = 0.027). After adjustment for previous mRS and ICH score, there were no differences in 3-month mortality or poor outcome at 3 months between sexes. Conclusions: Patients with ICH showed sex-related differences in demographic characteristics, ICH location, and vascular risk factors, but not in stroke care, 3-month mortality, or adjusted poor outcome.